Autologous haematopoietic stem cell therapy for multiple sclerosis: a review for supportive care clinicians on behalf of the Autoimmune Diseases Working Party of the European Society for Blood and Marrow Transplantation. Issue 4 (December 2019) - Ismail, Azza; Sharrack, Basil; Saccardi, Riccardo; Moore, John J.; Snowden, John A.
Abstract : Purpose of review: In this review, we summarize the recently published literature that demonstrates the efficacy and safety of autologous haematopoietic stem cell therapy (AHSCT) in multiple sclerosis (MS) and highlight the importance of supportive care required for the safe and well-tolerated delivery of AHSCT. Recent findings: MS is an autoimmune inflammatory and degenerative disorder of the central nervous system (CNS). In the majority of patients, the illness runs a relapsing remitting course (RRMS), culminating in a secondary progressive phase with gradual accumulation of fixed disabilities. Currently available disease-modifying therapies suppress CNS inflammation but have a limited effect on preventing disease progression for which there remains no effective therapy. Over the last two decades, there has been increasing evidence that AHSCT is a highly effective therapeutic strategy for treatment-resistant inflammatory types of MS, especially RRMS. Concerns about the safety of AHSCT in MS, usually a nonlife-threatening disease, have previously limited its use. However, AHSCT can now be delivered safely with major long-term benefits because of increasing transplant centre experience, judicious patient selection and good supportive care. Summary: MS is currently the fastest growing indication for AHSCT in Europe. Supportive care before, during and after the transplant period is key to the successful delivery of AHSCT.